Terapi Relaksasi Benson Termodifikasi Efektif Mengontrol Gula Darah pada Lansia dengan Diabetes Mellitus - Diah Ratnawati; Tatiana Siregar; Candra Tri Wahyudi (Jurnal Kedokteran dan Kesehatan, 2018)
Meditation in the Benson relaxation is a repetition of words/phrases, passive attitude is an essential things. Glucose reducement mechanism with this Benson relaxation happened by reducing physical stress and psychologic that will reduce epinephrin, reduce cortisol, reduce glucagon and reduce tyroid hormon. Modified Benson relaxation therapy intervention use a combination of meditation, deep breathing relaxation, and progresive muscle relaxation. This research aiming to analizing the effectiveness of Benson relaxation therapy on glucose. This research is a quasi experimental pre nd post tes with control group using elders in Puskesmas Limo area coverage who have diabetes mellitus as a research subject with a control group of 36 people and intervention group of 36 people that generated by purposive samping method. Data analysis by comparing before and after using modified Benson relaxation therapy on glucose using paired t-test and Mann Whitney statistical test. Result of the research show that there are significant changes on glucose on intervention group that given modified Benson relaxation therapy compared with control group that only given health education (p < 0,05). The effectivity of modified Benson relaxation therapy on glucose control on eldery with diabetes mellitus (p < 0,05). It is recommended so nurse can use modified Benson relaxation therapy as a intervention in controlling glucose on elder with diabetes mellitus. Keywords: modified Benson relaxation theraphy, glucose